(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the association of BMI and risk factors of coronary artery disease in patients presenting with chest pain in outdoor cardiology department. Study Design: Descriptive / comparative study Place and Duration of Study: This study was conducted at the Outdoor Cardiology Department of Nishter Hospital Multan from May 2016 to August 2016. Materials and Methods: All patients who presented with complain of chest pain in outdoor cardiology department were included. Patients were divided into three groups on the basis of BMI. SPSS V23 was used for data computation. Chi-square test and ANOVA test were used for comparison of variables between different BMI groups respectively. Results: There were 42.0% females patients in obese group as compared to only 12.0% and 20.0% in normal weight and overweight groups (p-value 0.002 Mean age of patients at the time of presentation was significantly less in obese group 49.38+6.56 years, whereas in normal and overweight patients mean age was 56.60+9.29 years and 54.84+9.94 years respectively (p-value <0.001). There was no patient with age more than 60 years in obese group, 47.5% in overweight group and 52.5% in normal weight group (p-value <0.001).There were higher number of hypertensive patients in overweight (56%) and obese group patients (58%) as compared to normal weight patients (p-value 0.03). Coronary artery disease was diagnosed in only 20.0% patients in normal weight patients, 24.0% in overweight patients and in 48.0% obese patients (p-value 0.005). Conclusion: Obesity is an independent risk factor for the early development of coronary artery disease (CAD) and increased risk of hypertension in early age.